Strategi Penguatan Ekonomi Orang Tua pada Keluarga Anak Jalanan di Surabaya - Puji Sucia Sukmaningrum; Siti Inayatul Faizah (JURNAL SOSIAL HUMANIORA (JSH), 2019)
This study aims to find out the strategy on how to strengthen the economic welfare of street children’s family in Surabaya. Children are the next generation of the nation whose all their needs should be fulfilled. Surabaya, as one of the largest cities in Indonesia, has some issues relating to poverty and street children. The research employed a qualitative research method, and the informants were the street children in Sanggar Alang-Alang Surabaya. The result of the study showed that the strategy that can be given to parents of the street children is the construction of the family workforce through the creative economy program, protection from discrimination against their work, provision of services, and creating productive business for poor families